Effects of Ibuprofen on the physiology and outcome of rabbit endotoxic shock - art. no. 26 - Celik, I; Akbulut, A; Kilic, SS; Rahman, A; Vural, P; Canbaz, M; Felek, S (Bmc, 2002)
Background: Despite major developments in the management of septic shock, the mortality rate had progressively increased. Ibuprofen has been shown to have beneficial physiological effects when used as a treatment. However, there are conflicting results with respect to survival. This study aims to investigate the effect of ibuprofen on vital functions, various physiological parameters and survival during endotoxic shock in rabbits. Methods: Twenty-eight New Zealand rabbits were randomly separated into four groups. The first group received only saline, the second was given 2 mg/kg intravenous endotoxin at t(0), the third received 30 mg/kg ibuprofen 30 minutes after endotoxin administration, whilst the fourth group received ibuprofen 30 minutes before the endotoxin. Respiratory and heart rate, mean arterial blood pressure and rectal temperature were recorded. Complete blood counts were performed and thromboxane B-2 was measured every 30 minutes for the first two hours, and then hourly over the course of the experiment. Urine samples were collected at the same time points for the measurement of prostaglandin E-2. Results: Ibuprofen was found to improve respiratory rate, heart rate, and arterial pressure. However, it did not improve the negative effects of endotoxin on body temperature, haematocrit values, white blood cell count, and thrombocyte number. Thromboxane B-2 levels in group IV were significantly lower than in the other groups, and the increase started at a later timepoint. In ibuprofen-treated animals, Prostaglandin E-2 levels stayed low for at least 90 minutes, but started to rise thereafter. While the average survival in Group II animals was 192.9 +/- 46.9 minutes, those of groups III and IV were 339.1 +/- 33.5 minutes (p < 0.05) and 383.0 +/- 39.6 minutes (p = 0.01), respectively. Conclusions: Ibuprofen appears to increase survival in endotoxic shock-induced animals. Therefore, it may be helpful for the prophylaxis and treatment of patients with, or who are likely to develop, septic shock.
Keywords: Acute Lung Injury; Cyclooxygenase Inhibition; Cardiovascular-Response; Normal Humans; Septic Shock; Sepsis; Survival; Failure; Therapy; Model